2013
DOI: 10.1371/journal.pone.0075975
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Increases Locomotion and Dopamine Transporter Activity in Dopamine D5 Receptor-Deficient Mice

Abstract: Dopamine regulates the psychomotor stimulant activities of amphetamine-like substances in the brain. The effects of dopamine are mediated through five known dopamine receptor subtypes in mammals. The functional relevance of D5 dopamine receptors in the central nervous system is not well understood. To determine the functional relevance of D5 dopamine receptors, we created D5 dopamine receptor-deficient mice and then used these mice to assess the roles of D5 dopamine receptors in the behavioral response to meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
(49 reference statements)
3
10
0
Order By: Relevance
“…To examine the possible behavioral consequences of these events, we stimulated D1/D5 receptors with SKF38393 before AMPH treatment to inhibit Rho activation and were able to block the effects of AMPHinduced hyperlocomotion as well as DAT surface expression. Consistent with this model, D5 knockout mice display enhanced locomotor activity in response to methamphetamine (25). However, our data also suggest that there is a component of psychostimulantinduced hyperlocomotion that is not Rho-mediated because the activation of D1/D5 receptors does not bring the AMPHinduced hyperlocomotion down to control levels, but rather to the level produced by cocaine.…”
Section: Discussionsupporting
confidence: 82%
“…To examine the possible behavioral consequences of these events, we stimulated D1/D5 receptors with SKF38393 before AMPH treatment to inhibit Rho activation and were able to block the effects of AMPHinduced hyperlocomotion as well as DAT surface expression. Consistent with this model, D5 knockout mice display enhanced locomotor activity in response to methamphetamine (25). However, our data also suggest that there is a component of psychostimulantinduced hyperlocomotion that is not Rho-mediated because the activation of D1/D5 receptors does not bring the AMPHinduced hyperlocomotion down to control levels, but rather to the level produced by cocaine.…”
Section: Discussionsupporting
confidence: 82%
“…Methamphetamine induced mice showed a body weight reduction as shown in table 1 the finding is supported by previous studies 16,17,22 . T h ym o q u i n o n e (T Q) s h o we d s i gn if ic a nt neuroprotective effects in hippocampal neurons in neurodegenerative effects of Alzheimer disease (AD), which is highly consistent with this study as Nigella sativa produced similar effects in the present study against methamphetamine induced injury 22 . Another previous study has reported neuroprotective effects of TQ significantly against hippocampus injury in experimental animals by increasing anti-oxidant enzyme activity 24 .…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, D5 KO mice respond normally to acute and chronic cocaine and present normal conditioned place preference in response to cocaine 19 . Interestingly, D5 KO are more sensitive to a methamphetamine, an effect that is mediated by the DA transporter 20 . Startle response and pre-pulse inhibition are normal in these mice.…”
mentioning
confidence: 97%